2021
DOI: 10.1056/nejmoa2102968
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Multisystem Inflammatory Syndrome in Children

Abstract: Background Evidence is urgently needed to support treatment decisions for children with multisystem inflammatory syndrome (MIS-C) associated with severe acute respiratory syndrome coronavirus 2. Methods We performed an international observational cohort study of clinical and outcome data regarding suspected MIS-C that had been uploaded by physicians onto a Web-based database. We used inverse-probability weighting and generalized linear models to evaluate intravenous imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
247
3
16

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 288 publications
(304 citation statements)
references
References 27 publications
6
247
3
16
Order By: Relevance
“…Several retrospective reviews support the clinical impression that myocardial function normalizes more quickly in children who receive corticosteroid with IVIG [ 65 , 66 , 67 •]. A single study suggesting a lack of benefit of corticosteroids in MIS-C included a subset of patients who did not meet a standard MIS-C case definition and were negative for SARS-CoV-2 antibody, making a diagnosis of SARS-CoV-2-related illness unlikely in these patients and complicating interpretation of the results [ 68 ]. The optimal dose of corticosteroid for MIS-C remains unknown, but in two studies, doses in the 1–2-mg/kg/day range were used [ 65 , 66 ]; many centers use a tapering dose regimen over a 2–3-week period.…”
Section: Treatmentmentioning
confidence: 99%
“…Several retrospective reviews support the clinical impression that myocardial function normalizes more quickly in children who receive corticosteroid with IVIG [ 65 , 66 , 67 •]. A single study suggesting a lack of benefit of corticosteroids in MIS-C included a subset of patients who did not meet a standard MIS-C case definition and were negative for SARS-CoV-2 antibody, making a diagnosis of SARS-CoV-2-related illness unlikely in these patients and complicating interpretation of the results [ 68 ]. The optimal dose of corticosteroid for MIS-C remains unknown, but in two studies, doses in the 1–2-mg/kg/day range were used [ 65 , 66 ]; many centers use a tapering dose regimen over a 2–3-week period.…”
Section: Treatmentmentioning
confidence: 99%
“…There is no definitive cure to date. The consequences of being infected with COVID-19 can be multi-faceted, such as multisystem inflammatory syndrome in children, acute multi-organ failure in adults, and long COVID-19 syndrome in all recoverees [2][3][4][5]. Global vaccination programs and multiple preventive measures are the most effective ways to curb rapid transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, it is known that, even if less frequently than in adults, children can develop a severe COVID-19. At higher risk are subjects with severe underlying medical conditions, younger children and those that develop the so-called multisystem inflammatory syndrome (MIS-C) [ 1 , 6 ]. Moreover, the review of the clinical picture of pediatric COVID-19 has shown that its impact extends beyond the pulmonary morbidity and mortality of the disease.…”
Section: Introductionmentioning
confidence: 99%